Koding Life: An Interactive Learning Media Innovation for Learning in Facilitating Students' Computational Thinking - Ayik Oktafia; Mardiana; Supianto (Universitas Pendidikan Ganesha, 2026)
Digital change in education necessitates the enhancement of digital literacy and computational thinking (CT) from primary education; however, learning practices in Indonesia remain predominantly conventional, with teachers exhibiting poor ICT proficiency. This circumstance renders coding education abstract and devoid of supportive digital resources tailored to student characteristics. This study seeks to create and evaluate the viability of the Koding LIFE digital learning media as a computational thinking-based coding educational resource for elementary school pupils. The study employs the Research and Development (R&D) approach, encompassing: (1) a preliminary investigation via observation and interviews to ascertain the needs of teachers and students; (2) the creation of visual-based interactive media; and (3) validation by experts and practicality assessment by teachers and students. The research participants were two media specialists, two material specialists, three educators, and sixteen students. Data were gathered by observation, interviews, and questionnaires, thereafter evaluated both qualitatively and quantitatively in a descriptive manner. The study's findings reveal that classroom learning is deficient in digital media integration, educators lack the capability to create coding media, and pupils require visual aids to comprehend algorithmic principles. The validation from media experts resulted in an average score of 3.67 (Very Feasible), whilst material experts assigned a score of 3.80 (Very Feasible). Assessments of teacher practicality and student feasibility demonstrated that the media was user-friendly, entertaining, and facilitated comprehension of CT principles. These findings hold significant implications for enhancing digital ecosystems in schools and creating pertinent coding resources for elementary education.